Disruptive innovation in global markets: Cross-industry differences in the impact of rising Chinese competitors - Williamson, Peter; Wan, Feng; Yin, Eden (International Journal of Social and Administrative Sciences, 2025)
The purpose of this paper is to assess the differential impact across 30 global industries of disruptive innovation from Chinese companies. The paper presents a model of disruptive innovation to identify the conditions under which Chinese competitors can win a substantial share of global markets at the expense of incumbents. Analysing data on the market share gains by Chinese companies among the top five competitors in each industry between 2006 and 2018 we show there are marked differences both in the extent of disruption and the speed with which this occurs. Based on case study evidence, the inter-industry differences appeared to be largely explained by a mix of the product and industry characteristics that influenced competitive efficacy of strategies commonly used by leading Chinese companies. We suggest that the threat of ongoing global market disruption from Chinese competitors should not be underestimated, not least because it is backed by well-developed, dynamic capabilities in cost and accelerated innovation and in accessing, absorbing and leveraging technologies and knowledge being generated throughout the world.